2018
DOI: 10.3201/eid2401.161555
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Canine-Mediated Human Rabies Death, Haiti, 2015

Abstract: In Haiti, an investigation occurred after the death of a 4-year-old girl with suspected rabies. With tips provided by community members, the investigation led to the identification of 2 probable rabies-related deaths and 16 persons bitten by rabid dogs, 75% of which chose postexposure prophylaxis. Community engagement can bolster rabies control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 6 publications
(7 reference statements)
4
8
0
Order By: Relevance
“…After the victim was bitten, it took almost two months before the onset of clinical signs while death ensued within 10 days following the noticeable symptoms. The incubation period observed in this case is consistent with 1-3 months previously stated by the World Health Organization, and also coincides with the results of other studies (World Health Organization, 2013;Wallace et al, 2016;Ahmad et al, 2017;Qi et al, 2018;Tran et al, 2018). Preceding reports have indicated a shorter incubation period in cases with category III exposure site on the upper limb (Wallace et al, 2016;Qi et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…After the victim was bitten, it took almost two months before the onset of clinical signs while death ensued within 10 days following the noticeable symptoms. The incubation period observed in this case is consistent with 1-3 months previously stated by the World Health Organization, and also coincides with the results of other studies (World Health Organization, 2013;Wallace et al, 2016;Ahmad et al, 2017;Qi et al, 2018;Tran et al, 2018). Preceding reports have indicated a shorter incubation period in cases with category III exposure site on the upper limb (Wallace et al, 2016;Qi et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Hence, this case can basically be classified as probable rabies. The recognized clinical signs and course of the illness in this case were similar to the previously reported exposures describing rabies in humans who died after being bitten by a suspected rabid dog (Wallace et al, 2016;Tran et al, 2018). Although the surveillance of rabies in humans has not been well carried out in Nigeria, the first documented rabies case in Zamfara State was detected in a sheep that had been bitten by an aggressive stray dog (Ahmad et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Haiti is one of the last remaining countries in the Western Hemisphere with endemic canine rabies [ 1 , 12 – 16 ]. From 2009–2012, an average of four canine and seven human rabies cases were reported by Haiti’s national surveillance system (NSS), however, studies have shown these reports underestimate the true burden of rabies [ 1 , 13 15 , 17 ]. One community-based surveillance program with active bite-case investigation, which was operated in three Haitian communes, detected more rabid animals than reported for the entire country by NSS [ 13 ].…”
Section: Introductionmentioning
confidence: 99%